Planktonic community in the phytotelmata of bromeliads (Bromeliaceae) in urbane environment of Feira de Santana, Bahia, Brazil - Silva, Márcio Borba da; Ribeiro, Maria José Rocha; Costa, Paulo Tadeu Silva (SITIENTIBUS série Ciências Biológicas, 2007)
This paper presents a checklist on the planktonic community found in bromeliads of gardens in the urban zone of Feira de Santana, with emphasis on the protists, thus diminishing the lack of taxonomic study about this community. The checklist was based on collections in the tank bromeliads (Vriesea sp. and Aechmea sp.) from four urbane areas of Feira de Santana, which had the stored water analysed in laboratory. Protists belonging to the Phylum Ciliophora (Chilodon sp., Colpoda sp., Euplotes sp., Loxodes sp., Oxytricha sp., Paramecium sp., Stylonychia sp., and Uronema sp.), to the subphylum Sarcodina (Arcella sp. and Difflugia sp.) and the subphylum Mastigophora (Astasia sp., Euglena sp., Peranema sp., Cryptomonas sp., Phacus sp., and Enthosiphon sp.), as well as Nematoda, Anellida (Oligochaeta) and microcrustacean (Ostracoda and Cladocera) were found. This survey illustrates the great aquatic diversity of organisms in this peculiar habitat, thus evidencing the importance for conservation and maintenance of these planktonic species.